2019
DOI: 10.3390/ijms20153709
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Deficiency Potentiates Thioacetamide-Induced Hepatic Fibrosis in Sprague-Dawley Rats

Abstract: Hepatic fibrosis is characterized by persistent deposition of extracellular matrix proteins and occurs in chronic liver diseases. The aim of the present study is to investigate whether estrogen deficiency (ED) potentiates hepatic fibrosis in a thioacetamide (TAA)-treated rat model. Fibrosis was induced via intraperitoneal injection (i.p.) of TAA (150 mg/kg/day) for four weeks in ovariectomized (OVX) female, sham-operated female, or male rats. In TAA-treated OVX rats, the activities of serum alanine aminotransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
3
18
1
1
Order By: Relevance
“…We found that TGF-β1-stimulated activation of ERK1/2 and p38 was also dose-dependently inhibited by melatonin, whereas JNK1/2 phosphorylation was not affected. Previous studies have shown that Smad and MAPK signaling pathways play an important role in EMT stimulated by TGF-β1 [31][32][33] and the development of liver fibrosis [34][35][36][37]. Taken together, these results suggest that melatonin prevents EMT stimulated by TGF-β1 in AML12 hepatocytes through suppression of Smad and MAPK signaling cascades.…”
Section: Discussionsupporting
confidence: 58%
“…We found that TGF-β1-stimulated activation of ERK1/2 and p38 was also dose-dependently inhibited by melatonin, whereas JNK1/2 phosphorylation was not affected. Previous studies have shown that Smad and MAPK signaling pathways play an important role in EMT stimulated by TGF-β1 [31][32][33] and the development of liver fibrosis [34][35][36][37]. Taken together, these results suggest that melatonin prevents EMT stimulated by TGF-β1 in AML12 hepatocytes through suppression of Smad and MAPK signaling cascades.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, it has been shown that estradiol influences HSC transdifferentiation/activation. In various models of liver fibrosis caused by carbon tetrachloride (CCl 4 ), dimethylnitrosamine (DMN), or thioacetamide (TAA), treatment with estradiol inhibited HSC proliferation/activation and decreased collagen production [162,163,164,165]. In addition, activated HSCs incubated with estradiol exhibited less myofibroblast-like phenotypes compared with those of vehicle-treated cells [166].…”
Section: Gender Differences In Nafld/nashmentioning
confidence: 99%
“…According to TAA treatment in ovary, accumulation of ECM in stromal cells nearby follicles is indicated in Masson Goldner trichrome staining and also based on decreased total number of follicles and increased number of atretic follicles ( Figure 1 ). Previously, TAA treated ovary induced oxidative stress levels, resulting in imbalance of sex hormones [ 6 ]. ROS acts as an important signaling factor in granulosa cells, but also causes apoptosis when it exceeds normal level [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thioacetamide (TAA) is a thinosulfur widely known as hepatotoxin that triggers liver damage by generating ROS [ 5 ]. Oxidative stress in liver induced by TAA can cause a wide spectrum ranging from acute hepatitis to cirrhosis [ 6 ]. TAA is metabolized by hepatic cytochrome (CYP) 450 and generate TAA S-dioxide which is the active product that produce reactive oxygen species (ROS) factors and production of TGF-ß [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%